Evaluasi Tata Kelola Teknologi Informasi Bidang Aplikasi Dan Informatika Dinas Komunikasi Dan Informatika Kabupaten Madiun Dengan Menggunakan Kerangka Kerja COBIT 4.1 Pada Domain Deliver and Support (DS) dan Monitor and Evaluate (ME) - Rahmania Kumalasari; Yusi Tyroni Mursityo; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Government agencies have the duties and authority of the regions regarding the field of communication and informatics is Diskominfo Kabupaten Madiun. There are fields in Diskominfo carrying out its duties, one of the fields namely application and informatics has the task of preparing technical policies, programs, monitoring, evaluation and reporting. Diskominfo Kabupaten Madiun needs a good IT governance in order to have IT service management in accordance with the objectives and carry out organizational tasks with COBIT 4.1 in the domain of delivery and support (DS) focused on service and monitor and Evaluate (ME) focused on IT governance. The purpose of this study is to measure the value of maturity level and the value of the gap (GAP analysis) between current conditions (as-is) and expected values (to-be). Determination of respondents using the RACI chart mapping and data collection by observation and interview. Based on the data obtained the results obtained by the DS domain maturity value of 1.97 and ME domain maturity of 2.02 are at the 2.07 repeatable level. And for the gap in the target to be achieved DS8 and DS13 sub-domains are 2.00 and the other DS sub-domains are 1.00. For the ME domain that is to be reached at the 1.00 level. Proposed recommendations in the form of formal SOPs and best practices in order to achieve existing IT services and governance in the application and information technology fields are achieved. A DS2 subdomain recommendation consists of periodic monitoring management documentation, risk analysis documentation, third party performance monitoring documentation. In the ME4 domain, designing an IT governance management plan, drafting regulations understanding IT problems faced by all parties, evaluating and reporting governance management, and establishing a forum on IT governance management.